Analysis of the Village Head's Leadership Style in Management of Digital-Based Services at the Village Office - Zulfikar, Zulfikar; Sundari, Sundari; Adnan, Andi Astinah (Jurnal Studi Ilmu Pemerintahan, 2024)
This study examines the leadership style of the village head in managing digital-based services at the village office. Using both qualitative and quantitative methods, the research reveals that the village head's leadership style significantly impacts the effectiveness of digital services. Inclusive leadership, characterized by respect and acceptance, facilitates digital services but lacks delegation and centralized decision-making processes. However, charismatic leadership, characterized by respect and decision-making finesse, is praised for its ability to navigate complexity. The office workforce, particularly in delivering digital-based services, is effective and efficient, improving service quality and community satisfaction. High employee motivation drives quality service delivery, and the office's technological infrastructure, including a fast internet network, enhances service delivery processes. The study underscores the importance of considering leadership dynamics in village governments to optimize digitally oriented services. However, its generalizability is limited as it focuses on the village head's leadership style. Future research should explore the interaction between leadership style and other organizational determinants, such as staff competencies and technological infrastructure.